Effects of galantamine on smoking behavior and cognitive performance in treatment‐seeking smokers prior to a quit attempt. (21st June 2018) - MacLean, Robert Ross; Waters, Andrew J.; Brede, Emily; Sofuoglu, Mehmet
Abstract: Objective: Drugs that enhance cholinergic transmission have demonstrated promise treating addictive disorders. Galantamine, an acetylcholinesterase inhibitor, may reduce cigarette smoking in otherwise healthy treatment‐seeking smokers. Methods: The current study is a double‐blind, placebo‐controlled, study that randomized daily smokers ( n  = 60) to receive one of two doses of galantamine extended release (8 or 16 mg/day), or a placebo treatment. Participants completed a smoking choice task as well as study measures and cognitive tasks in the laboratory and daily life using ecological momentary assessment. Analysis focused on smoking behavior and satisfaction, cognitive performance, and decision to smoke prior to a quit attempt. Results: Linear mixed models demonstrated that, compared with placebo, both doses of galantamine reduced smoking in a laboratory choice task ( p  = 0.006) and decreased urine cotinine levels, but not self‐reported cigarettes, during the pre‐quit period ( p  = 0.007). Treatment had minimal effect on smoking satisfaction or cognitive performance. Conclusions: The results suggest that galantamine reduces nicotine intake but it is unlikely that galantamine improves cognitive performance in otherwise healthy, treatment‐seeking smokers. Larger randomized clinical trials can determine if galantamine adjunctive to addiction treatment can improve smoking treatment outcomes.